Single-column cryogenic air separation: Enabling efficient oxygen production with rapid startup and low capital costs—application to low-carbon fossil-fuel plants. (15th November 2021) - Cheng, Mao; Verma, Piyush; Yang, Zhiwei; Axelbaum, Richard L.
Highlights: The PSC-ASU can save up to 19% on capital costs compared with the double-column ASU. The PSC-ASU can reduce energy cost by 14.5% compared with Linde's single-column ASU. The pressure ratio of the main air compressor is 21% lower than that of the double-column ASU. The PSC-ASU is more cost-effective when applied in a low-carbon, fossil-fuel power plant. Abstract: The rapid integration of intermittent renewable sources into the electricity grid is driving the need for more flexible, low-carbon fossil-fuel plants with lower capital costs. This then drives the need to improve the cryogenic air separation unit (ASU). To address this changing landscape, we explore a Praxair single-column ASU (PSC-ASU) design with the goal of reducing costs and improving flexibility, compared to a conventional double-column ASU. The PSC-ASU incorporates partial air condensation and air pre-separation in the bottom reboiler with a phase separator as well as N2 -enriched vapor condensation in the upper reboiler to decrease energy consumption, as compared to Linde's single-column ASU. All three of the above-mentioned ASU designs are simulated in Aspen Plus and analyzed. An economic analysis is applied to evaluate the relative cost savings of the PSC-ASU compared to the double-column ASU. Results suggest that the specific energy consumption of the PSC-ASU is significantly lower than that of Linde's single-column ASU due to a drastically improved oxygen recovery rate. Although this improved oxygen recovery rate is still lower than that of the double-column ASU, the required pressure ratio of the main air compressor is 21% lower than that of the double-column ASU. As a result, the specific energy consumption of the PSC-ASU is only 1.9% greater than that of the double-column ASU for producing 95.1 mol% O2 . However, the PSC-ASU reduces the hourly capital cost by 19% due to the elimination of a high-pressure column. This would effectively decrease the total hourly cost of the ASU, and thus the total hourly cost of low-carbon, fossil-fuel power plants that require oxygen.